A METHOD FOR APPROXIMATING SOLUTION OF ORDINARY DIFFERENTIAL EQUATIONS BY USING FUZZY TRANSFORMS - Halder, S. B.; Das, P. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
Fuzzy transforms developed by Irina Perfilieva is a novel, mathematically well founded soft computing tool with many applications. These techniques are based on mainly two transforms, direct fuzzy transform and inverse fuzzy transform. However a lot of works has still to be done on it for e.g. the extension of fuzzy transform and its applications in ordinary differential equations. In this paper we develop an approximating model based on fuzzy transform and apply the model for numerical solution of ordinary differential equations.